1998
DOI: 10.1523/jneurosci.18-03-00923.1998
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Superoxide Contribute to Motor Neuron Apoptosis Induced by Trophic Factor Deprivation

Abstract: Primary cultures of rat embryonic motor neurons deprived of brain-derived neurotrophic factor (BDNF) induce neuronal nitric oxide synthase (NOS) within 18 hr. Subsequently, >60% of the neurons undergo apoptosis between 18 and 24 hr after plating. Nitro-L-arginine and nitro-L-arginine methyl ester (L-NAME) prevented motor neuron death induced by trophic factor deprivation. Exogenous generation of nitric oxide at concentrations lower than 100 nM overcame the protection by L-NAME. Manganese tetrakis (4-benzoyl ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
259
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(282 citation statements)
references
References 65 publications
17
259
0
4
Order By: Relevance
“…45 In this case, L-NAME or L-nitro-arginine actually inhibited apoptosis and supported survival of the motor neurons deprived of BDNF. L-NAME protection was abolished by excess L-arginine.…”
Section: Neuronsmentioning
confidence: 87%
“…45 In this case, L-NAME or L-nitro-arginine actually inhibited apoptosis and supported survival of the motor neurons deprived of BDNF. L-NAME protection was abolished by excess L-arginine.…”
Section: Neuronsmentioning
confidence: 87%
“…At low concentrations NO can protect cells against oxidative stress, presumably by induction of adaptive responses in the form of up-regulation of antioxidant proteins (43,44). In contrast, inhibition of nNOS has been shown to protect rat motor neurons from cell death induced by oxidative stress (45). The findings that inhibition of nNOS in a cell culture model of FALS did not confer resistance to mutant SOD1 toxicity (46) and that blockade of NOS either by chemical means (47) or targeted deletion of the nNOS gene (48) had little effect on disease progression in a transgenic mouse model of human ALS have raised uncertainties regarding the importance of NO production in ALS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…13 An excessive NO production has cytotoxic effects and induces neuronal apoptosis secondary to neural degeneration and neurodysfunction. 14 Several disorders are associated with oxidative stress that are manifested by LP, protein oxidation and other markers. A study by Liu et al 15 reported that oxidative stress levels increase markedly during the first weeks of strict immobilization after the onset of an SCI.…”
Section: Oxidative Stress and Scimentioning
confidence: 99%